Soluble HLA-associated peptide from PSF1 has a cancer vaccine potency - Yoshida, Mari; Ishioka, Yukichi; Ozawa, Takamasa; Okuyama, Hirohisa; Iguchi, Motofumi; Ota, Takeshi; Ito, Takaomi; Nagira, Morio; Morita, Atsushi; Tanaka, Hidekazu; Naito, Hisamichi; Kidoya, Hiroyasu; et al. (Scientific reports, 2017)
Partner of sld five 1 (PSF1) is an evolutionary conserved DNA replication factor involved in DNA replication in lower species, which is strongly expressed in normal stem cell populations and progenitor cell populations. Recently, we have investigated PSF1 functions in cancer cells and found that PSF1 plays a significant role in tumour growth. These findings provide initial evidence for the potential of PSF1 as a therapeutic target. Here, we reveal that PSF1 contains an immunogenic epitope suitable for an antitumour vaccine. We analysed PSF1 peptides eluted from affinity-purified human leukocyte antigen (HLA) by mass spectrometry and identified PSF1 79–87 peptide (YLYDRLLRI) that has the highest prediction score using an in silico algorithm. PSF1 79–87 peptide induced PSF1-specific cytotoxic T lymphocyte responses such as the production of interferon-γ and cytotoxicity. Because PSF1 is expressed in cancer cell populations and highly expressed in cancer stem cell populations, these data suggest that vaccination with PSF1 79–87 peptide may be a novel therapeutic strategy for cancer treatment.